Labour supply response of a retirement earnings test reform - Erik Hernæs; Zhiyang Jia (University of Oslo, Department of Economics, 2009)
Norwegian administrative data are used to evaluate the impact of a doubling of the threshold in the earnings test on the labour force activity. We find no impact on labour market participation, but positive effects on earnings. The effect increases with exposure to the reform and is stronger for individuals with earnings around the threshold and with high education. Individuals who remain active until retirement age respond more to the reform than those who left labour force earlier. The results indicate both substantial labour supply responsiveness among elderly, and heterogeneity with respect to preferences, labour market options or both.
Keywords: J14; H55; 330; Retirement earnings test; Benefit entitlement; Labour supply behaviour; Heterogeneity; Altersgrenze; Gesetzliche Rentenversicherung; Ältere Arbeitskräfte; Arbeitsangebot; Norwegen